Anxiety-related experience-dependent white matter structural differences in adolescence: A monozygotic twin difference approach - Nagesh Adluru (Nature Portfolio, 2017)
Abstract Anxiety is linked to deficits in structural and functional connectivity between limbic structures and pre-frontal cortices. We employed a monozygotic (MZ) twin difference design to examine the relationship between structural characteristics of the uncinate fasciculus (UF) measured by Diffusion Tensor Imaging (DTI) and anxiety symptoms in a sample of N = 100 monozygotic (genetically identical), adolescent twins. The MZ difference design allowed us focus on environmental factors that vary within twin pairs while controlling for genetic and environmental factors shared by twin pairs. Twins aged 13–18 years reported on symptoms of generalized anxiety and social phobia prior to participating in a neuroimaging visit. Regions of interest from the JHU ICBM atlas, including uncinate fasciculus and sagittal stratum as a control tract, were registered to the study template. We incorporated multiple diffusion tensor measures to characterize the white matter differences. Within twin pairs, the more anxious twin exhibited decreased fractional anisotropy (t = −2.22, p = 0.032) and axial diffusivity (t = −2.38, p = 0.022) in the left UF compared to the less anxious twin, controlling for age and gender. This study demonstrated the feasibility and advantages of adopting the MZ twin design for DTI measures in neuroimaging research.